Cardiac Safety in Breast Cancer Patients Receiving Pegylated Liposome Doxorubicin Sequential Anti-HER2 Monoclonal Antibody Therapy - Huang, Ping; Huang, Jia-huan; Zheng, Ya-bing; Cao, Wen-ming; Shao, Xi-ying; Chen, Jun-qing; Huang, Yuan; Li, Guang-liang; Sharma, K; Zhou, Huan-huan; Wang, Xiao-jia; Jin, Hong-chuan; et al. (Frontiers in Pharmacology, 2022)
Background: Cardiotoxicity associated with the sequential use of anthracyclines followed by trastuzumab is common in adjuvant therapy of patients with HER2-positive early breast cancer (eBC). However, the cardiac safety of trastuzumab concurrent with pegylated liposomal doxorubicin (PLD) is relatively less studied. Method: Clinical data of patients with HER2-positive eBC treated with PLD and cyclophosphamide (PLD-C) followed by taxanes plus trastuzumab ± pertuzumab (TH or TPH) who then completed standard anti-HER2 treatment for 12 months from June 2012 to August 2021 were retrospectively collected. The primary endpoints were clinical and subclinical cardiotoxicity. Result: In total, 70 eligible patients were enrolled. Among them, 55 patients (78.6%) received PLD-C → TH and 15 patients (21.4%) received PLD-C → TPH. The median follow-up time was 41.8 months. Until August 2021, only two patients had recurrent or metastatic diseases, with 2-year and 5-year disease-free survivals of 98.6% and 96.8%, respectively. Clinical cardiotoxicity occurred in six patients (8.6%), and all of them had an absolute decline of ≥16% from baseline left ventricular ejection fraction (LVEF) but not below the lower limit of normal (LLN = 50%). Subclinical cardiotoxicity events occurred in 17 patients (24.3%), and all of them had absolute declines of ≥10% and <16% from baseline LVEF but not below the LLN. No patients were interrupted from treatment, and all patients completed anti-HER2 treatment for 12 months. The sharpest decrease in LVEF was observed at 18 months after the start of PLD treatment. The cumulative incidences of clinical and subclinical cardiotoxicity were 9.8% and 28.3%, respectively. In the univariate analysis, body mass index, age, left chest wall radiotherapy, and ongoing cardiovascular risk factors were not significantly associated with clinical or subclinical cardiotoxicity (p > 0.05). No patients had congestive heart failure or death caused by PLD or anti-HER2 treatment. Conclusion: The sequential use of PLD and trastuzumab showed a lower incidence of clinical cardiotoxicity, presented as asymptomatic decreased LVEF, compared with the results obtained in previous clinical studies using conventional anthracycline, taxanes and trastuzumab. The study regimen demonstrated good cardiac tolerance and is an alternative strategy for cardioprotection in patients with HER2-positive eBC.